2023
DOI: 10.30935/cedtech/13419
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of artificial intelligence technology in an academic writing class: How do Indonesian students perceive?

Abstract: Research shows that artificial intelligence (AI) technology positively influences students’ writing skills, but this area has yet to be touched by Indonesian researchers. This study aims to map perception, obstacles, and recommendations for optimizing use of AI in teaching academic writing in Indonesian. This article focuses on a case study of three senior high schools in Central Java, Indonesia. It employs quantitative and qualitative data. The researcher collected the data using questionnaires presented with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
21
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 45 publications
7
21
0
Order By: Relevance
“…This heightened engagement in writing activities potentially contributed to the development of the learners' academic writing skills. These findings align with the research of Utami and Winarni (2023), who also found that AI-powered language learning tools improved EFL learners' engagement in writing activities, consequently leading to improvements in writing skills. The qualitative findings of the current study further corroborated these quantitative findings, as learners exhibited positive responses toward the integration of the AI-assisted language learning approach into their writing activities.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This heightened engagement in writing activities potentially contributed to the development of the learners' academic writing skills. These findings align with the research of Utami and Winarni (2023), who also found that AI-powered language learning tools improved EFL learners' engagement in writing activities, consequently leading to improvements in writing skills. The qualitative findings of the current study further corroborated these quantitative findings, as learners exhibited positive responses toward the integration of the AI-assisted language learning approach into their writing activities.…”
Section: Discussionsupporting
confidence: 90%
“…These quantitative findings resonate with the observations made by Liu et al (2021) and Yan (2023), who underscored the profound contributions of AI-assisted language learning tools in advancing EFL learners' writing abilities. Moreover, these findings harmonize with the outcomes identified by Rahman et al (2022) and Utami and Winarni (2023), which accentuated the positive influence of AI-powered language learning on EFL learners' motivation and their heightened engagement in writing tasks.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations